Multiplex detection of five common respiratory pathogens from bronchoalveolar lavages using high resolution melting curve analysis - Jaber Ghorbani (BMC Microbiology, 2022)
Abstract Background The study describes the application of the multiplex high-resolution melting curve (MHRM) assay for the simultaneous detection of five common bacterial pathogens (Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii and Escherichia coli) directly from bronchoalveolar lavage samples. Results Our MHRM assay successfully identified all five respiratory pathogens in less than 5 h, with five separate melting curves with specific melt peak temperatures (Tm). The different Tm were characterized by peaks of 78.1 ± 0.4 °C for S. aureus, 83.3 ± 0.1 °C for A. baumannii, 86.7 ± 0.2 °C for E. coli, 90.5 ± 0.1 °C for K. pneumoniae, 94.5 ± 0.2 °C for P. aeruginosa. The overall sensitivity and specificity of MHRM were 100% and 88.8–100%, respectively. Conclusions Our MHRM assay offers a simple and fast alternative to culture approach for simultaneous detection of five major bacterial lower respiratory tract infection pathogens. Utilization of this assay can help clinicians initiate prompt and appropriate antimicrobial treatment, towards reducing the morbidity and mortality of severe respiratory infections.